Anti-Corruption Tools of Financial Risk Management in Public Administration - Kopanchuk, Volodymyr; Kravchuk, Oleh; Torichnyi, Vadym; Metil, Anastasiia; Kurtsev, Oleksii; Kopanchuk, Olena (International Journal of Innovative Research and Scientific Studies, 2021)
Every country is concerned with the problem of corruption. Selfish misuse of public office undermines the people's confidence in government and institutions, makes public policies less effective and fair, and misuses taxpayer funds that could be used to build schools, roads and hospitals. Financial risk management in public administration is based on risk assessments and finding tools to help influence them. To develop practical tools for financial risk management, the authors studied the economic practises that determine the features of financial risk assessment. They identified the elements that can motivate financial risks, including three stages of identification and analysis of risks, analyzed the main stages and indicators of assessing an organization's financial condition based on the balance sheet, produced a risk assessment algorithm and risk minimization methods in managing financial activities, and conducted a comparative analysis of financial risk assessment methods. Based on the Professional Integrity Framework proposed by the Organization for Economic Cooperation and Development, the authors developed basic measures to mitigate the potential negative consequences and proposed seven financial risk management tools for public administration. The proposed anti-corruption tools will help significantly reduce financial risks in public administration and corruption in general.